2023
DOI: 10.1111/raq.12862
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of dysbiosis in fish microbiomes in the context of aquaculture

Raquel Xavier,
Ricardo Severino,
Sofia M. Silva

Abstract: Fish microbiome plays an important role in maintaining host homeostasis, with many bacterial functions directly linked to host fitness. Fish microbiome research is advancing fast, especially in the context of aquaculture where several stressors are known to disrupt stability of host‐associated bacteria, prompting dysbiosis. Therefore, understanding the signatures of dysbiosis in different fish mucosae and their association with such stressors is fundamental to set up efficient health‐monitoring strategies, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 193 publications
2
6
0
Order By: Relevance
“…This suggests a lower effect of this antibiotic in disrupting fish skin microbiome compared to Nitrofurazone but could also be indicative of a resistance against this antibiotic. These results are in accordance with the review of Xavier et al (2024), who found that despite the low number of existing studies, quinolones do not frequently alter the alpha-diversity of fish microbiomes. Moreover, they are consistent with results of Zheng et al, 2014).…”
Section: Most Abundant Taxa and Differential Abundant Asvssupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests a lower effect of this antibiotic in disrupting fish skin microbiome compared to Nitrofurazone but could also be indicative of a resistance against this antibiotic. These results are in accordance with the review of Xavier et al (2024), who found that despite the low number of existing studies, quinolones do not frequently alter the alpha-diversity of fish microbiomes. Moreover, they are consistent with results of Zheng et al, 2014).…”
Section: Most Abundant Taxa and Differential Abundant Asvssupporting
confidence: 92%
“…Moreover, they are consistent with results of Zheng et al, 2014). Indeed, increases in Vibrio and other Vibrionaceae are frequently reported in studies investigating the effects of quinolones in fish microbiomes (Xavier et al, 2024).…”
Section: Most Abundant Taxa and Differential Abundant Asvsmentioning
confidence: 97%
“…Many studies have dealt with the in uence of abiotic stress on the gut and skin microbiota in sh, usually under arti cial rearing conditions (Bell et al, 2024). However, despite its huge potential for health monitoring, gill compositions are largely overlooked (Sehnal et al, 2021;Xavier et al, 2024), especially along physicochemical gradients in an estuarine system.…”
Section: Discussionmentioning
confidence: 99%
“…Another problem of excessive use of antibiotics, reported in recent years, is the effect on the composition of the intestinal microbiota of salmonids. Antibiotics generate dysbiosis in the intestine of fish, which causes changes in various biological processes, including the immune response ( Donati et al, 2022 ; Huyben et al, 2023 ; Xavier et al, 2023 ). The problem of excessive use of antibiotics has been recognized by Chilean salmon producers, so in 2019, the salmon farming sector and the Monterey Bay Aquarium launched the Chilean Salmon Antibiotic Reduction Program (CSARP) with the aim of reducing the use of antibiotics by 50% by 2025.…”
Section: Introductionmentioning
confidence: 99%